1992
DOI: 10.1139/g92-115
|View full text |Cite
|
Sign up to set email alerts
|

A genetic linkage map of restriction fragment length polymorphism loci for Brassica rapa (syn. campestris)

Abstract: A genetic linkage map has been constructed based on restriction fragment length polymorphism DNA markers for Brassica rapa L. using a segregating F2 progeny from a cross between the yellow sarson type 'R500' and the canola-type 'Horizon'. The map contains 360 marker loci detected by 269 genomic clones derived from a PstI library of 'Westar' (Brassica napus L.). The map consists of 10 linkage groups, covering a total of 1876 recombination units. The occurrence of substantial genome rearrangement during the evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…Several flowering-time genes from Arabidopsis (2 loci/2 probes), B. rapa (7 loci/6 probes), and BrMyrosinase, BrDFRI, BrGST, BrSAM, and BrSLP (10 loci/5 probes) functional genes were mapped on this linkage map. The detection of 1.31 loci per RFLP probe (520/396) closely matches that reported (1.27 and 1.34 from 220 and 269 probes, respectively) for previous B. rapa maps (Song et al 1991;Chyi et al 1992). In contrast, Udall et al (2005) observed a higher level of polymorphism with codominant and dominant segregation in the amphidiploid B. napus, where there are twice as many potential loci.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several flowering-time genes from Arabidopsis (2 loci/2 probes), B. rapa (7 loci/6 probes), and BrMyrosinase, BrDFRI, BrGST, BrSAM, and BrSLP (10 loci/5 probes) functional genes were mapped on this linkage map. The detection of 1.31 loci per RFLP probe (520/396) closely matches that reported (1.27 and 1.34 from 220 and 269 probes, respectively) for previous B. rapa maps (Song et al 1991;Chyi et al 1992). In contrast, Udall et al (2005) observed a higher level of polymorphism with codominant and dominant segregation in the amphidiploid B. napus, where there are twice as many potential loci.…”
Section: Discussionsupporting
confidence: 88%
“…The high degree of neutral DNA polymorphisms of most Brassica species (Figdore et al 1988) has facilitated the development of molecular linkage maps, with at least 15 described to date for B. oleracea (Slocum et al 1990;Kianian and Quiros 1992;Lan et al 2000), B. rapa (Song et al 1991;Chyi et al 1992;Teutenico and Osborn 1994), B. nigra (Lagercrantz and Lydiate 1996), B. Juncea (Cheung et al 1997;Pradhan et al 2003), and B. napus (Landry et al 1991;Uzunova et al 1995). Where common sets of DNA markers and/or parental genotypes have been used, it has been possible to designate linkage groups according to a common nomenclature (Parkin et al 1995(Parkin et al , 2005Butruille et al 1999;Sebastian et al 2000).…”
Section: T He Genus Brassica Includes Oilseed Vegetablementioning
confidence: 99%
“…The Brassica probes tested would be suitable for characterizing the addition and trisomic lines developed from the current material CHENG et al 1993CHENG et al , 1994aCHENG et al ,b, 1995a. Various Brassica probes have been used in the analysis of B. campestris-alboglabra addition lines or segregating F, populations, which has yielded a number of linkage maps for B. oleracea (SLOCUM et al 1990;HU and QUIROS 1991;LANDRY et al 1992;KIANIAN and QUIROS 1992b;FIGDORE et al 1993;KENNARD et al 1994;TEUTONICO and OSBORN 1994) and for B. campestris (SONG et al 1991;CHYI et al 1992;TEUTONICO and OSBORN 1994). The combination of RFLP markers with isozyme and morphological traits has been instrumental in constructing linkage maps for B. campestris and B. oleracea (HOSAKA et al 1990;QUIROS 1990, 1991a;KIANIAN and QUIROS 1992b).…”
Section: Discussionmentioning
confidence: 99%
“…Linkage maps, of variable saturation extents, have been developed for the A and C genomes of Brassica when applying restriction fragment length polymorphism (RFLP), random amplified polymorphic DNA (RAPD), and DNA fingerprinting (QUIROS et al 1987(QUIROS et al , 1994DELSENY et al 1990;HOSAKA et al 1990;SLOCUM et al 1990; HU and QUIROS 1991; MC- GRATH andQUIROS 1991a, 1992;SONG et al 1988SONG et al , 1991CHYI et al 1992; KIANIAN and QUIROS 1992a,b;LANDRY et al 1992;KENNARD et al 1994;POULSEN et al 1994). In addition to the linkage mapping of different molecular markers, these investigations gave us insight into the occurrence of gene duplications, chromosome structural changes and intergenomic gene introgression.…”
mentioning
confidence: 99%
“…Molecular mapping of B. rapa was initiated by Song et al (1991) using RFLP markers and a segregating F 2 population. Subsequently several additional maps were constructed based on different molecular markers and F 2 , recombinant inbred lines (RILs) or DH populations (Chyi et al 1992;Teutonico and Osborn 1994;Kole et al 1997;Suwabe et al 2006;Kim et al 2006;Choi et al 2007). The recent development of Brassica simple sequence repeat (SSR) markers facilitates the anchoring of linkage groups to one common reference map and allows the comparison of map positions in studies involving different populations (Suwabe et al 2006;Choi et al 2007).…”
Section: Introductionmentioning
confidence: 99%